Effect of Amount and Type of Fuel on The Smoked Fish Quality - Sandi Asmara; Oktafri; Tamrin; Putri Windasari (Open Global Scientific Journal, 2022)
Indonesia has a diverse range of fish species in both seawater and freshwater. Lampung is one of the provinces in Indonesia that has a rich diversity of fish species. Lampung has a wide variety of fish species, including tilapia. Tilapia is a food material that decomposes quickly due to bacteria and microorganisms. As a result, one of them is the need for profitable handling by utilizing smoking technology. Smoked fish is popular in Lampung, but the most commonly used fuel is coconut shell, coconut coir, and corn cobs. The use of common fuel in the community still cannot assess the smoking fuel that can produce good quality standards of fish. As a result of the aforementioned issues, the research was to evaluate effect of fuel quantity and type on the quality of smoked fish. The goal of this study is to determine the effect of fuel amount on tilapia smoking, the type of fuel that can produce smoked fish of optimal quality, and the cost of fuel needed for tilapia smoking using coconut shell fuel, coconut coir, and corn cobs. The method used in this study was organoleptic testing on 25 panelists using a smoked fish score sheet determined by SNI smoked fish, and then the panelists' scores were processed using excel. The amount of fuel used and the duration of smoking have no effect on the quality value of smoked fish, and the type of fuel that can produce smoked fish of optimal quality, namely coconut coir, passed the SME (export quality certificate)  standard with an organoleptic value of smoked fish of 8.0.